Evaluation of Probiotic Properties of Lactic Acid Bacteria Isolated from Fermented Fish - Sriphannam, Chayaphon; Kummasook, Aksarakorn (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020DO - 10.14456/nujst.2020.10, 2020)
The present study describes the potential probiotic lactic acid bacteria isolated from fermented fish. A total of 23 isolates of lactic acid bacteria were purified using MRS medium. All the isolates were assessed for tolerance to low pH. It was observed that only 4 isolates (UP2, UP9, UP16, and UP20) could survive at pH 2. These isolates further evaluated in vitro for bile salts tolerance, NaCl tolerance, phenol tolerance, antagonistic activity, b-Galactosidase production, and cell surface hydrophobicity. Based on results, all selected isolates possessed a b-galactosidase and showed an ability to tolerate in bile salt, NaCl, and phenol. Among 4 selected LABs, isolates UP 20 and UP2 showed the higher cell hydrophobicity as 81% and 68.8%, respectively. These results indicate that isolate UP20 and UP2 might be useful as probiotics. However, further studies may be performed to confirm their potential health benefits and applications. Keywords: probiotic properties, lactic acid bacteria, fermented fish